Fundamentals of engineering mechanics - Levinson, L. (Moscú: Mir, 1970)
Theoretical mechanics: introduction - Statics: Basic concepts of forces. Introduction to statics - Coplanar systems of intersecting forces - Coplanar parallel forces. The moment of a force - Centre of gravity. Stability of bodies - Friction. Kinematics: The trajectory of a particle. Distance and time - Rectilinear motion of a particle - Composition of simple motions of a particle - Curvilinear motion of a particle - Simple motions of a solid body. Dynamics: Funtamentals - Fundamentals of dynamics of a material point - Work and power - Mechanical energy. Theory of machines and fundamentals of strain. Theory of machines : Introduction. Machines and mechanisms - The inclined plane, pulley and windlass - Transmissions between parallel shafts - Transmissions between non-parallel shafts - Conversion of rotation into linear translation and viceversa - Auxiliary parts used in transmitting rotation - Detachable connections. Strength of materials: Basic principles - Tension and compression - Shear and torsion - Bending - General principles of combined strains - Appendix
Keywords: MECANICA TEORICA; CINEMATICA; DINAMICA; TEORIA DE MAQUINAS; DEFORMACIONES; RESISTENCIA